A fluorescent probe for alkylating agents and its quantification of triflate as a genotoxic impurity. Issue 15 (1st February 2023) - Zhang, Dan; Wang, Sifan; Yang, Fangxi; Qi, Qingrong; Li, Yanfang; Huang, Wencai
Abstract : A fluorescent probe for the selective and sensitive detection of ethyl triflate, a genotoxic impurity, was developed and its application in fludarabine was demonstrated. Abstract : The responses of a reaction-based fluorescent probe BI-Py towards alkyl halide, epoxide, carbonate, sulfate, sulphonate and triflate were evaluated and the probe achieved selective detection of ethyl triflate in acetonitrile with a LOD of 1.08 μM. BI-Py exhibited great potential for detecting triflate as a genotoxic impurity in drug substances.